Entrepreneurial Behaviours of Farm Women from Baghpat District, Uttar Pradesh - Shivani Singh, Premlata Singh, Satyapriya (Indian Journal of Extension Education, 2023)
Providing food security has been focus of the Government’s planning and policy. Food security meansavailability of sufficient foodgrains to meet the domestic demand as well as access, at the individual level,to adequate quantities of food at affordable prices. Attainment of self-sufficiency in foodgrains productionat the national level has been one of the major achievements of the country. Addressing food securitycannot only be done by creating awareness about nutrition and healthy food, capacity building interventionsbut to take it to another level an entrepreneurial approach is highly recommended. Global changes havecreated economic opportunities and women entrepreneurs have emerged as a distinct class. Their contributionto national economy is now substantial. Women entrepreneurship directly or indirectly decides the Nation’seconomy and its growth, In India the development in women entrepreneursnip had come a long way sinceit was systematically initiated in early 80s.To understand the attitude and acceptance of farm women thisinline study was conducted in Mukari and Lehchhoda villages of Baghpat district Uttar Pradesh with 60farm women. The results revealed that two third (58.33%) of farm women belongs to medium entrepreneurialbehavior.Socio economic factors such as : Education, land holding, annual income, economic motivationand attitude towards value addition of agricultural produce and business aspect in agri-nutri food productsshows positive and only information found negatively significant relationship with entrepreneurial behaviour.Whereas other variables like interest in learning and soci-economic status has been studied.